Hopelessness and Dejection but Still Struggling! Exploring Power Dynamics and Resistance in Colonial Resistance Poetry in Mahmoud Darwish’s Poem ’Speech of the Red Indian’ - Syeda Maria Johar; Sabah Aziz; Hira Rafiq (University of Chitral Journal of Linguistics and Literature, 2023)
This research aims to shed light on the misuse of power by colonial authorities and the resultant resistance asserted by colonized people in Mahmoud Darwish’s poem "Speech of the Red Indian.” Mahmud Darwish generally is known as Palestine’s most famous nationalistic poet. The research study adopts a qualitative approach. In addition to this, Fairclough’s 3-dimensional analytical framework has assisted in providing an effective and nuanced comprehension of the struggle and power dynamics disclosed in the poem. At the textual level, Michael Halliday’s transitivity analysis has been employed for a deeper understanding of exhumed patterns. The study identifies certain transitivity processes such as material, relational, verbal, existential, and mental in the clauses of the poem. The patterns reveal linguistic construction aimed at conveying the nature of power working underline, resistance, and struggle of colonized people, consequently categorizing the text as anti-colonial discourse. The poem reveals a creative way of Darwish that transcends a provocative imperial discourse and discloses their unjustified rule on people. Furthermore, this text will offer an opportunity to understand the real power struggle of colonized people in the current context.